Male Infertility Knowledgebase: decoding the genetic and disease landscape. (7th August 2021) - Joseph, Shaini; Mahale, Smita D
Abstract: Male infertility is a multifactorial condition that contributes to around one-third of cases of infertility worldwide. Several chromosomal aberrations, single-gene and polygenic associations with male factor defects have been reported. These defects manifest as sperm number or sperm quality defects leading to infertility. However, in almost 40% of cases, the genetic etiology of male infertility remains unexplained. Understanding the causal genetic factors is crucial for effective patient management and counseling. Integrating the vast amount of available omics data on male infertility is a first step towards understanding, delineating and prioritizing genes associated with the different male reproductive disorders. The Male Infertility Knowledgebase (MIK) is a manually curated repository developed to boost research on the elusive genetic etiology of male infertility. It integrates information on ∼17 000 genes, their associated pathways, gene ontology, diseases and gene and sequence-based analysis tools. In addition, it also incorporates information on reported chromosomal aberrations and syndromic associations with male infertility. Disease enrichment of genes in MIK indicate a shared genetic etiology between cancer, male and female infertility disorders. While the genes involved in cancer pathways were found to be common causal factors for sperm number and sperm quality defects, the interleukin pathways were found to be shared and enriched between male factor defects and non-reproductive conditions like cardiovascular diseases, metabolic diseases, etc. Disease information in MIK can be explored further to identify high-risk conditions associated with male infertility and delineate shared genetic etiology. Utility of the knowledgebase in predicting novel genes is illustrated by identification of 149 novel candidates for cryptorchidism using gene prioritization and network analysis. MIK will serve as a platform for review of genetic information on male infertility, identification pleiotropic genes, prediction of novel candidate genes for the different male infertility diseases and for portending future high-risk diseases associated with male infertility. Database URL : http://mik.bicnirrh.res.in/